Gamelan online: implementation of image map technique / Norizuan Paimin - Paimin, Norizuan (2010)
In relatively recent times, gamelan music has begun to accompany secular events, including tourist and concert performances, government functions and educational demonstrations. The majority of music traditions were preserved by oral transmission of rhythms and melodies from generation to generation and there not preserve in digital. This study aims to find ways to assist the young generation in order to show and introducing them for traditional Malaysian music in a more attractive way by using web page. This study can make them enjoy while listening to the song and at the same time can gain their knowledge. One the development of application is focused on applications targeted to the end-user, the usability extreme importance because it is one of the key factors for user acceptance of an application.